Development of Learning Strategy-based Training Programs - Esilvita, Esilvita (Universitas Negeri Padang, 2023)
Education and training are key elements in developing human resources to achieve progress and success in various areas of life. In this context, the Education and Training Program (Training and Education is an abbreviation for Education and Training) becomes an important approach in meeting the learning needs and development of individual and group competencies. Developing a learning strategy-based training program (Diklat) is a strategic step in ensuring that the training provided can have a positive and effective impact on participants. In this ever-developing era, education and training have a very important role in improving the quality of human resources. Therefore, the use of appropriate learning strategies is the main key in designing training programs that are relevant and can stimulate the development of participant competencies. The method used to create this article was a quantitative approach. Meanwhile, the type of research carried out is literature review. In learning strategy-based training, training participants will also be given the opportunity to practice implementing effective learning strategies through simulations and role plays. This aims to enable them to practically understand how to manage the learning process and provide a meaningful learning experience for training participants.